VR Road and Construction Site Safety Conceptual Modeling Based on Hand Gestures - Côté, Stéphane; Beaulieu, Olivier (Frontiers in Robotics and AI, 2019)
Engineering road design and construction site safety design can be lengthy processes, incompatible with situations where only a conceptual design is required, and/or when required by users unfamiliar with such complex pieces of software. In this study, an intuitive road design VR application based on hand gesture was proposed and developed as a proof of concept. Results show the resulting application is easy, natural and fun to use, and could represent a good alternative to more complex design applications.